Known for My Work : African American Ethics from Slavery to Freedom - Morgan, Lynda J. (Book collections on Project MUSE., 2016)
"Lynda Morgan builds an intellectual and social history of slave thought about labor and morality, and she traces elements through Reconstruction and the civil rights movement. She concludes her manuscript by connecting this legacy to reparations arguments and apologies for slavery that continue in the present day"--Provided by publisher